ANALYSIS OF GOOD MANUFACTURING PRACTICE (GMP) IMPLEMENTATION: A CASE STUDY IN TWO CANNED SARDINELLA PROCESSING INDUSTRIES IN EAST JAVA - Dewi, Reza Putri Amalia; Tanjung, Anasri; Soeprijadi, liliek; Napitupulu, Romauli Juliana; weni, Weni (Politeknik Kelautan dan Perikanan Karawang, 2026)
Good Manufacturing Practices (GMP) serve as a fundamental framework for ensuring the quality and safety of fishery products. Nevertheless, their implementation in fish processing industries is often found to be suboptimal, including in sardine canning operations involving Sardinella lemuru. This study aimed to assess the level of GMP implementation in two lemuru canning industries located in East Java. Data were collected from October to November 2025 through field observations, document reviews, and interviews with quality control personnel and supervisors. The evaluation was carried out using a gap analysis approach, in which the GMP assessment criteria were based on the Ministry of Marine Affairs and Fisheries Regulation (Permen KP) No. 17 of 2019. The findings indicate that both industries have implemented GMP in accordance with the applicable standards, achieving conformity levels of 94.97% for lemuru products in tomato sauce and 89.33% for products packed in water, salt, and oil. However, of the 15 GMP aspects evaluated, three nonconformities were identified in both tomato-based canned products and products packed in water, salt, and oil. Several aspects were found to require improvement, particularly those related to site and building conditions, floor and wall structures, and ceiling or roofing conditions